An Investigation of the Demand for Financial Advice in China's Retail Investment Markets - Ren, Haowei (2006)
In recent years, there are more and more investment products available on the Chinese financial retail market. Such as bonds, unit trusts, life and health insurances, futures and foreign currencies etc. They are relatively new and complex to ordinary Chinese individuals. It is not easy to just understand all these products, how to use them is even harder. So people start to consider: maybe I should ask a professional investment advisor in person.